Analisis kinerja rantai pasok dalam sistem patron klien komoditi rumput laut Di Kabupaten Bombana - Rifka; Mansyur, Akhmad; Annaastasia, Nurhuda; Siang, Roslindah Daeng; Nurdiana A (Jurnal Sosial Ekonomi Perikanan, 2024)
The seaweed supply chain is a series of physical network activities of seaweed supply actors by actors involved in supplying, producing seaweed, and delivering it to end users. This study aims to determine; how the supply chain channel pattern and supply chain performance of seaweed commodities. This research was conducted in Bombana Regency from December 2022 to January 2023. Respondents in this study consisted of 1 collecting trader, 5 collecting traders and 5 seaweed farmers, which were determined by snowball sampling. Data were analyzed descriptively to answer the objectives of how the channel pattern and supply chain performance of seaweed commodities in Kabupaten Bombana. The results showed that the channel pattern of the seaweed supply chain in the client patron system in Kabupaten Bombana has two channels, namely (1) the cultivator to the collecting trader, then to the collecting trader, (2) the cultivator to the collecting trader. Furthermore, the performance of the seaweed supply chain in the client patron system is seen from the value of marketing margin and farmer's share which is divided into 2 channels. For channel I, namely; (1) marketing margin of seaweed type Eucheuma spinosum IDR 700,000 and type Eucheuma cottoni IDR 800,000, then (2) farmer's share of seaweed type Eucheuma spinosum 53.33% and type Eucheuma cottoni 73.33%. Then for channel II, namely; (1) marketing margin of seaweed type Eucheuma spinosum IDR 500,000 and Eucheuma cottoni type IDR 500,000, then (2) farmer's share of seaweed type Eucheuma spinosum 66.67% and seaweed type Eucheuma cottoni 83.33%. So that the marketing efficiency of the seaweed supply chain shows that the highest marketing margin is in channel I, while from the results of the analysis of the highest farmer's share is in channel II.